A Configurational Approach to Family Firm Innovation. (June 2019) - Kosmidou, Vasiliki; Ahuja, Manju K.
This article develops an integrated framework for the examination of innovation drivers in small and privately owned family firms. Drawing from the family-driven innovation model, we study how factors at the family, the firm, and the environment level combine into distinct configurations that spur innovation. Analyzing 277 family firms using fuzzy-set qualitative comparative analysis, we find six configurations leading to high innovation and show that none of the antecedents is necessary for it. Building inductively on our configurations, we also derive propositions about the combinations of factors leading to high innovation. Implications for research and practice are discussed.